Baby-Sitters Little Sister: Karen's Kittycat Club - Book 4 2, Karens roller skates - Farina, Katy; Lamb, Braden; Martin, Ann M., 1955- (New York, New York : Graphix, an imprint of Scholastic, 2020)
When Karen shows off her roller-skating expertise and accidently crashes into her brother, she ends up with a broken wrist but uses the opportunity to get everyone she knows to sign her new cast.
Series numbering from spine.
a"Based on the novel by Ann M. Martin"--Cover.
Keywords: Roller skating -- Comic books, strips, etc; Autographs -- Comic books, strips, etc; Brothers and sisters -- Comic books, strips, etc; Roller skating -- Fiction; Autographs -- Fiction; Brothers and sisters -- Fiction; Comics (Graphic works); Graphic novels